Ionospheric Disturbances Recorded by DEMETER Satellite over Active Volcanoes: From August 2004 to December 2010 - Jacques Zlotnicki; Feng Li; Michel Parrot (International Journal of Geophysics)
The study analyzes electromagnetic data and plasma characteristics in the ionosphere recorded by DEMETER microsatellite over erupting volcanoes during the life of the mission: from August 2004 to December 2010. The time window in which anomalous changes are searched brackets the onset of the eruptive activity from 60 days before to 15 days after the period during which most pre- and posteruptive phenomena are amplified. 73 volcanoes have entered into eruption. For 58 of them, 269 anomalies were found in relation to 89 eruptions. They are distributed in 5 types, similarly to the ones observed above impeding earthquakes. The two main types are electrostatic turbulence (type 1, 23.4%) and electromagnetic emissions (type 2, 69.5%). The maximum number of types 1 and 2 anomalies is recorded between 30 and 15 days before the surface activity, corresponding to the period of accelerating phenomena. The amount of anomalies seems related to the powerfulness of the eruptions. The appearance seems dependant on the likelihood to release bursts of gases during the preparatory eruptive phase. For the huge centenary October 26, 2010, Merapi (Indonesia) eruption, 9 ionospheric type 2 anomalies appeared before the eruption. They mainly emerge during the mechanical fatigue stage during which microfracturing occurs.